Effect of hybrid nano particle reinforcements on fractographic, mechanical and wear behavior of Al6061 alloy composites manufactured by ultrasonic assisted stir casting technique - Annapoorna Krishnappa; Shobha Ramesh; Bharath Vedashantha Murthy; Rajanna Siddagangappa; Srimadhu Ashokkumar; Madeva Nagaral; Virupaxi Auradi (Fracture and Structural Integrity)
The purpose of this study is to investigate the influence of hybrid nanoparticle reinforcement with Al2O3 and ZrO2 on the mechanical and wear parameters of Al6061 alloy-based Nano composites. MMCs (Metal Matrix Composite) specimens were produced using an ultrasonic-assisted stir casting method. Al6061 with varying weight percentages of Al2O3 (0.5%, 0.75%, 1% and 1.25%) and ZrO2 (0.5%, 0.75%, 1% and 1.25%) were used as reinforcement. The fabricated samples were made to undergo various tests as per ASTM standards to evaluate tensile strength, hardness and wear properties. Scanning Electron Microscopy was used to analyze the microstructure of the produced nano composite to ascertain the distribution of Al2O3 and ZrO2 nano particles and to analyze the fractured and wear characteristics. The results indicate that there is increase in tensile behavior for the composition of Al6061matrix alloy reinforced with 1wt. % Al2O3 and 1wt. % ZrO2 hybrid reinforcement. The maximum hardness achieved was 90.9 Hv with 1% ZrO2 and 1.25% Al2O3, representing a significant improvement over pure aluminum. The prepared specimens were subjected to a wear test utilizing a pin-on-disc machine and results reveal that highest wear resistance was obtained for the hybrid reinforcement of 1wt.% Al2O3 and 1wt.% ZrO2 with Al6061 alloy matrix